Computational Investigation of Antifouling Property of Polyacrylamide Brushes - Liu, Yonglan; Zhang, Dong; Ren, Baiping; Gong, Xiong; Liu, Aristo; Chang, Yung; He, Yi; Zheng, Jie (Langmuir, 2020)
Antifouling materials and coatings have broad fundamental and practical applications. Strong hydration at polymer surfaces has been proven to be responsible for their antifouling property, but molecular details of interfacial water behaviors and their functional roles in protein resistance remain elusive. Here, we computationally studied the packing structure, surface hydration, and protein resistance of four poly(N-hydroxyalkyl acrylamide) (PAMs) brushes with different carbon spacer lengths (CSLs) using a combination of molecular mechanics (MM), Monte Carlo (MC), and molecular dynamics (MD) simulations. The packing structure of different PAM brushes were first determined and served as a structural basis for further exploring the CSL-dependent dynamics and structure of water molecules on PAM brushes and their surface resistance ability to lysozyme protein. Upon determining an optimal packing structure of PAMs by MM and optimal protein orientation on PAMs by MC, MD simulations further revealed that poly(N-hydroxymethyl acrylamide) (pHMAA), poly(N-(2-hydroxyethyl)acrylamide) (pHEAA), and poly(N-(3-hydroxypropyl)acrylamide) (pHPAA) brushes with shorter CSLs = 1–3 possessed a much stronger binding ability to more water molecules than a poly(N-(5-hydroxypentyl)acrylamide) (pHPenAA) brush with CSL = 5. Consequently, CSL-induced strong surface hydration on pHMAA, pHEAA, and pHPAA brushes led to high surface resistance to lysozyme adsorption, in sharp contrast to lysozyme adsorption on the pHPenAA brush. Computational studies confirmed the experimental results of surface wettability and protein adsorption from surface plasmon resonance, contact angle, and sum frequency generation vibrational spectroscopy, highlighting that small structural variation of CSLs can greatly impact surface hydration and antifouling characteristics of antifouling surfaces, which may provide structural-based design guidelines for new and effective antifouling materials and surfaces.